The lace-sheet-weavers—a long story (Araneae: Psechridae: Psechrus) - Bayer, Steffen (Zootaxa, 2012)
Various publications of the last twelve years have shown that the species richness of the genus Psechrus is much higherthan was assumed 30 years ago. Based upon trends in the structures of the copulatory organs, for the first time, eight spe-cies groups are recognised and, including the present study, 46 species are now known. 20 species are recognised anddescribed as new: P. ulcus sp. nov., P. aluco sp. nov., P. decollatus sp. nov., P. elachys sp. nov., P. norops sp. nov., P.arcuatus sp. nov., P. laos sp. nov., P. inflatus sp. nov., P. pakawini sp. nov., P. demiror sp. nov., P. jaegeri sp. nov., P.vivax sp. nov., P. obtectus sp. nov., P. fuscai sp. nov., P. clavis sp. nov., P. hartmanni sp. nov., P. zygon sp. nov., P. tauri-cornis sp. nov., P. crepido sp. nov. and P. schwendingeri sp. nov. Two species are removed from synonymy with P. sin-gaporensis Thorell, 1894: P. annulatus Kulczyński 1908 (stat. nov.) and P. libelti Kulczyński 1908 (stat. nov.). One juniorsynonym of P. tingpingensis Yin, Wang & Zhang, 1985 is recognised: P. xinping Chen, Zhang, Song & Kim, 2002 (syn.nov.). New records are reported: P. libelti from Thailand, Malaysia & Brunei; P. ancoralis Bayer & Jäger, 2010 from Thai-land; P. himalayanus Simon, 1906 from Bhutan; P. ghecuanus Thorell, 1897 from Laos. Pre-epigynes/pre-vulvae of 20Psechrus species are examined and illustrated. In these species they apparently exhibit consistent and species-specificcharacters. However, since in several species only one subadult female was available for examination and in 57% of thePsechrus species even none at all, the characters of the pre-epigyne/pre-vulva are not included in the Psechrus identifica-tion key introduced herein. Additional information on the biology of Psechrus—for which the trivial name “lace-sheetweavers” is introduced herein—is provided.